THE ROLE OF LOCAL ELITE IN STRENGTHENING THE EXISTENCE OF INDIGENOUS COMMUNITIES IN BUNTU PEPASAN, NORTH TORAJA - Rompon, Reinsart Sampe; Sudarmono, Sudarmono (Jurnal Politik Pemerintahan Dharma Praja, 2024)
This study seeks to explain how local elites in Buntu Pepasan District support indigenous communities. This qualitative study uses in-depth interviews with official, religious, and civil elites in the local area. The research shows how each elite group supports indigenous populations. Formal elites preserve and recognize indigenous rights. Religious elites support indigenous communities morally and spiritually and uphold their values. However, civic elites and traditional leaders preserve and nurture local culture and customs. The position dimensions of each local elite reveal that they are a party that preserves cultural heritage and indigenous populations. Regarding to their reputation, local elites are trusted by the community to manage and sustain indigenous communities and use their influence to strengthen them. Furthermore, these insights can help create better indigenous community sustainability policies.